The Role of Waqf in Promoting Family-Owned Businesses among Married Women in Northeastern Nigeria - Adamu Abubakar Muhammad; Adam Muhammad Ardo; Shafa’at Ahmad Aliyu; Adama Lawal Tafida (Research Synergy Foundation, 2024)
This study investigates how waqf helps married women in northeastern Nigeria start family-owned enterprises. In the past, waqf, an Islamic charitable endowment, has supported underprivileged communities financially and with resources, acting as a mechanism for socioeconomic development. In this regard, waqf institutions can enable married women to start and maintain family-owned enterprises, tackling issues like restricted financial resources, socio-cultural constraints, and unstable economic conditions. By offering interest-free loans, training courses, and infrastructure assistance, waqf can encourage married women to start their own businesses, increasing their financial independence and boosting household income. The study uses qualitative research methodology, reviewing relevant literature on the subject matter and stakeholder interviews. Findings revealed that integrating waqf with family-owned business initiatives improves economic stability, reduces poverty levels, and strengthens family cohesion. Additionally, the study highlighted the need for strategic collaboration between waqf institutions, government bodies, and community organizations to optimize resource allocation and expand the impact of waqf on women's entrepreneurship. This research underscores the transformative potential of waqf in advancing gender-inclusive economic development in Northeastern Nigeria and provides recommendations for policymakers and waqf administrators to enhance the effectiveness of their programs.